2017
DOI: 10.1111/j.1755-3768.2017.02323
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence lifetime imaging ophthalmoscopy

Abstract: a b s t r a c tImaging techniques based on retinal autofluorescence have found broad applications in ophthalmology because they are extremely sensitive and noninvasive. Conventional fundus autofluorescence imaging measures fluorescence intensity of endogenous retinal fluorophores. It mainly derives its signal from lipofuscin at the level of the retinal pigment epithelium. Fundus autofluorescence, however, can not only be characterized by the spatial distribution of the fluorescence intensity or emission spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 106 publications
(148 reference statements)
1
20
0
Order By: Relevance
“…At each visit, a standardized sequence of investigations was performed for every patient including a general ophthalmological examination with a measurement of the BCVA (Early Treatment Diabetic Retinopathy Study [ETDRS] letters) [12]. Maximal pupil dilation was achieved using tropicamide 0.5% and phenylephrine HCl 2.5%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At each visit, a standardized sequence of investigations was performed for every patient including a general ophthalmological examination with a measurement of the BCVA (Early Treatment Diabetic Retinopathy Study [ETDRS] letters) [12]. Maximal pupil dilation was achieved using tropicamide 0.5% and phenylephrine HCl 2.5%.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescence lifetime imaging ophthalmoscopy (FLIO) is a relatively novel noninvasive imaging modality in clinical use for identification of metabolic alterations in different retinal diseases [12]. The FLIO technique is based on the preliminary work of Schweitzer et al and has the ability to identify fluorophores originating from the photoreceptor layer [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…[61][62][63] Studies have indicated that eyes with AMD have longer mean AF lifetimes compared with age-matched controls. Specifically, areas of complete outer retinal and RPE atrophy associated with GA have demonstrated long lifetimes likely due to fluorophore emission from the underlying choroid and connective tissue components, while eyes with RPE atrophy but remaining photoreceptor segments have displayed shorter fluorescence lifetimes.…”
Section: Multicolor Confocal Scanning Laser Ophthalmoscopymentioning
confidence: 99%
“…[58][59][60] Fluorescence Lifetime Imaging Ophthalmoscopy Fluorescence lifetime imaging ophthalmoscopy (FLIO) is a novel noninvasive imaging modality providing in vivo measurement of the lifetimes of endogenous retinal fluorophores and is closely related to FAF. [61][62][63] When photons from an external light source are applied to excite endogenous fluorophores of the retina, the fluorophores achieve a higher level of energy before returning to their ground state, and the average time between these two events can be quantified as the fluorescence lifetime. While conventional FAF provides spatial-resolved information on fluorescence intensities, FLIO additionally measures fluorescence lifetimes; thus, providing both space and time resolution.…”
Section: Multicolor Confocal Scanning Laser Ophthalmoscopymentioning
confidence: 99%
“…2,11,12 Fluorescence lifetime imaging ophthalmoscopy (FLIO) can identify early retinal changes in degenerative retinal diseases and has been shown to provide not only information about the integrity of the RPE but of the photoreceptors as well. [13][14][15][16][17][18][19][20][21][22] FLIO measures the lifetime time span of naturally occurring retinal fluorophores on excitation with a blue laser light impulse. Fluorescence lifetimes are specific for each molecule.…”
mentioning
confidence: 99%